Short-lasting unilateral neuralgiform headache attacks with conjunctival injection and tearing (SUNCT) responsive to intranasal lidocaine and nerve blockage: a case report - Teixeira, Daniel; Borelli, Wyllians Vendramini; Mantovani, Gabriel paulo; Castilhos, Raphael Machado; Londero, Renata (Headache Medicine, 2022)
Abstract Background: Trigeminal autonomic cephalalgias comprehend a myriad of headaches with different symptoms, with comprehend short-lasting unilateral neuralgiform headache attacks with cranial autonomic symptoms (SUNA) or with conjunctival injection and tearing (SUNCT). Current treatment options are limited, and they are based mostly on case reports and small studies. Case Report: We report here the case of a 75 years old man suffering from acute trigeminal autonomic headache with a satisfying response to intranasal lidocaine and nerve blockage. Conclusion: Intranasal lidocaine and nerve blockage may represent a useful and costeffective treatment for patients with SUNCT/SUNA.